Visual rhythm-based time series analysis for phenology studies - Almeida, Jurandy; Dos Santos, Jefersson A.; Alberton, Bruna C. [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP]; Da S. Torres, Ricardo (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Plant phenology has gained importance in the context of global change research, stimulating the development of new technologies for phenological observation. In this context, digital cameras have been successfully used as multi-channel imaging sensors, providing measures to estimate changes on phenological events, such as leaf flushing and senescence. We monitored leaf-changing patterns of a cerrado-savanna vegetation by taken daily digital images. For that, we extract leaf color information and correlated with phenological changes. In this way, time series associated with plant species are obtained, raising the need of using appropriate tools for mining patterns of interest. In this paper, we present a novel approach for representing phenological patterns of plant species. The proposed method is based on encoding time series as a visual rhythm, which is characterized by color description algorithms. A comparative analysis of different descriptors is conducted and discussed. Experimental results show that our approach presents high accuracy on identifying plant species. © 2013 IEEE.
Keywords: digital cameras; image analysis; remote phenology; time series; visual rhythm